Cardiac Catheterization in Children with Pulmonary Hypertensive Vascular Disease: Consensus Statement from the Pulmonary Vascular Research Institute, Pediatric and Congenital Heart Disease Task Forces. (1st March 2016) - del Cerro, Maria Jesus; Moledina, Shahin; Haworth, Sheila G.; Ivy, Dunbar; Dabbagh, Maha Al; Banjar, Hanaa; Diaz, Gabriel; Heath‐Freudenthal, Alexandria; Galal, Ahmed Nasser; Humpl, Tilman; Kulkarni, Snehal; Lopes, Antonio; et al.
Abstract : Cardiac catheterization is important in the diagnosis and risk stratification of pulmonary hypertensive vascular disease (PHVD) in children. Acute vasoreactivity testing provides key information about management, prognosis, therapeutic strategies, and efficacy. Data obtained at cardiac catheterization continue to play an important role in determining the surgical options for children with congenital heart disease and clinical evidence of increased pulmonary vascular resistance. The Pediatric and Congenital Heart Disease Task Forces of the Pulmonary Vascular Research Institute met to develop a consensus statement regarding indications for, conduct of, acute vasoreactivity testing with, and pitfalls and risks of cardiac catheterization in children with PHVD. This document contains the essentials of those discussions to provide a rationale for the hemodynamic assessment by cardiac catheterization of children with PHVD.